Binocular Training Reduces Amblyopic Visual Acuity Impairment. (March 2014) - Mansouri, B.; Singh, P.; Globa, A.; Pearson, P.
Abstract Amblyopia is the most common cause of monocular visual impairment. Patching, which is modestly effective, is the current treatment of amblyopia in children. There is no clinically approved treatment for adults. The present study is a clinical trial (non-sham controlled and non-randomized) that assessed the efficacy of binocular training for improvement of the visual acuity in children and adults with amblyopia. Twenty-two amblyopic subjects ranging in age from 5 to 73 (mean: 36.2) years for whom patching and/or surgical treatments did not correct their visual impairment completed an average of 14.5 sessions of binocular training over a period of 4 to 6 weeks. Random dot kinematograms were presented dichoptically to the two eyes and the participants' task was to identify the direction of motion of the targets. Mean visual acuity improvement was 0.34 LogMAR (range: 0.1–0.58 LogMAR) and was shown to persist 6 months following the cessation of binocular training. Our study provides results in a large number of patients that confirm the clinical effectiveness of binocular training as a treatment for amblyopia in improving visual acuity in both children and adults. Moreover, this study is the first to demonstrate that the improvements in visual function were maintained for 6 months in the absence of any additional treatment.